Pengaruh Customer Online Review dan Tagline Gratis Ongkir Terhadap Keputusan Pembelian Onlive Via E-Commerce Shopee (Studi pada Mahasiswa di Fakultas Ekonomi Universitas Negeri Medan) - Salsabillah, Talitha; T. Teviana (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the influence of Customer Online Review and Free Shipping Tagline on the purchasing decisions of Shopee customers, especially students at the Faculty of Economics, State University of Medan. The increasing phenomenon of online shopping, especially through the Shopee platform, has raised interest in knowing what factors influence consumer purchasing behavior. The method used in this study is a quantitative approach with multiple linear regression analysis techniques to test the effect of each independent variable on the dependent variable. Based on the results of the analysis, it was found that Customer Online Review did not have a significant effect on purchasing decisions, with a t-value of 1.921 smaller than t-table 1.989 and a significance value of 0.56> 0.05. On the other hand, the Free Shipping Tagline has a positive and significant effect on purchasing decisions, indicated by a t-value of 3.509> t-table 1.989 and a significance of 0.001 <0.05. Simultaneously, both variables, namely Customer Online Review and Free Shipping Tagline, have a positive and significant influence on purchasing decisions, with an Fcount value of 7.205 greater than Ftable 2.30 and a significance of 0.001 <0.05. The results of this study indicate that promotional marketing strategies such as Free Shipping are more effective in driving purchasing decisions than online reviews from other customers. Therefore, e-commerce companies such as Shopee need to put more emphasis on promotional strategies that provide direct benefits to consumers.